Frequency of Mucocutaneous Manifestions in HIV Infected Patients (Medical Forum Monthly, 2023)
Objective: To determine the frequency of mucocutaneous manifestations in patients presenting with HIV infection.Study Design: Descriptive cross-sectional studyPlace and Duration of Study: This study was conducted at the Dermatology Department, Family Care Center HIV, and Medicine & Allied Unit of Hayatabad Medical Complex Hospital, Peshawar from 12/1/2019 to 12/7/2019.Materials and Methods: All the mentioned information including age, gender, duration of disease, socioeconomic status, occupation, education level and marital status were recorded in pre designed proforma.The data was analyzed in SPSS version 21.Results: In this study, mean age was 32 years with SD ± 3.51. 62% patients were male while 38% patients were female. About 80% patients of HIV infection had mucocutaneous manifestations, which was statistically significant while 20 % patients did not have mucocutaneous manifestations of HIV/AIDS infection.Conclusion: This study concluded that the prevalence of mucocutaneous manifestations in patients with HIV infection is substantially high, therefore all HIV patients should be evaluated by a dermatologist.